Model for the phycobilisome rod with interlocking disks based on domain-weighted linker-polypeptide sequence homologies of Mastigocladus laminosus. (2000) - Parbel, Axel; Scheer, Hugo
Abstract : The 8 linker-polypeptides from the cyanobacterium Mastigocladus laminosus were examined by comparative amino-acid sequence analysis for the predicted domain structure reported in the literatur (Glauser 1991, Esteban 1993) in detail using split sequences for the rod, rod-core and for the repeats from the core-membrane linker-polypeptide( L cm 127.6 ) . This analysis gives two distinct domains, where domain 1 (∼ 22 kDa, identity between 31 and 70%) is present in the N-terminal two thirds of the class II linkers (∼ 30 kDa) and in the repeats of theL cm 127.6, and domain 2 (∼ 10 kDa, identity between 28 and 41%) in the C-terminal part of the class II rod linkers (L r 31 .5 andL r 32 .5 ) and in the two capping linkers (L c 7 .7 andL r 8 .2 ). Based on these data, X-ray structure analysis from phycobiliproteins and proteolysis experiments, an interlocking model for the phycobilisome rod organization is proposed, with linkers protruding from one phycobilisome disk into the neighbouring one.